Scarface - Trail, Armitage 1902-1930; Tandler, Adolph (<<The>> Criterion Collection, 2024)
"Blazing across the screen in a spray of bullets, the gangster-film sensation Scarface helped set the standard for the genre for decades to come. Swaggering, scary, and unexpectedly charming, Paul Muni gives an iconic portrayal of criminal sociopathy as Tony Camonte, the ruthless, machine-gun-toting mobster who rises through the ranks of a bootlegging empire atop an ever-increasing body count, but whose possessive relationship with his wild-child sister (Ann Dvorak) threatens to be his undoing. With rat-a-tat command of editing and dialogue, and his trademark panache, director Howard Hawks creates an unstoppable sense of dynamism while pushing on-screen violence to new heights of brutality." [criterion.com]
Original: USA 1932
4K UHD + Blu-ray special edition features: new 4K digital restoration, with uncompressed monaural soundtrack ; one 4K UHD disc of the film and one Blu-ray with the film and special features ; alternate ending, from the censored version of the film ; new conversation with author Megan Abbott and actor Bill Hader ; new interview with film scholar Lea Jacobs on director Howard Hawks’s innovative use of sound and editing ; English subtitles for the deaf and hard of hearing ; plus: An essay by critic Imogen Sara Smith
Keywords: Film